COST CONTROLLED AS APPLIED TO THE SMALLER BUSINESS ORGANIZATION. - Benninger, L. J. (The Accounting Review, 1956)
Abstract Difficulty in utilizing cost control devices in the small business lies in a misunderstanding of the nature of cost control. Too often thinking on cost control is interwoven with some rather elaborate historical or standard cost system. Further, those who take the view that the income statement does not purport to and cannot present a picture of operating efficiency becloud the problem. Cost control has but one object and that is assisting management to attain its goals. It is axiomatic that an organization has control over its costs only when its management wants to control costs. Conversely, when management lacks interest in cost control, costs remain uncontrolled. It is management's function, among a great many others, to establish a profit goal. A wide awake management will look ahead and attempt to come to some conclusion as to what it is after and what it can reasonably hope to obtain. To achieve its profit goal, management must inaugurate a systematic plan of assuring proper expenditure and must establish upper and lower limits of expenditure. Finally, it will need to put its plan into effect at all levels of management from the top to the bottom of the organization.